Advancements in noninvasive koala monitoring through combining Chlamydia detection with a targeted koala genotyping assay - H. K.A. Premachandra; Carme Piza-Roca; Andrea Casteriano; Damien P. Higgins; Katrin Hohwieler; Daniel Powell; Romane H. Cristescu (Scientific Reports)
Abstract Wildlife diseases are major players in local and global extinctions. Effective disease surveillance, management and conservation strategies require accurate estimates of pathogen prevalence. Yet pathogen detection in wild animals remains challenging. Current gold standards often require samples collected through veterinary examination, but this method is costly, intensive, invasive, and requires specialised staff and equipment. Collection of non-invasive samples, such as scats, is an effective monitoring tool which can be deployed at large scale, as scats contain DNA of both host and pathogens. The koala (Phascolarctos cinereus) is listed as ‘endangered’ under the EPBC Act 1999, with chlamydial disease representing a major threat. Here, we present a new approach that combines restriction-enzyme associated sequencing and targeted-sequence-capture genotyping, namely DArTcap, to detect Chlamydia pecorum in koala scats. We found this method has similar accuracy to current gold standards (qPCR of swab samples), with a sensitivity of 91.7% and a specificity of 100%. This method can be incorporated into existing koala genetic studies using marker panels, where population attributes can be estimated alongside C. pecorum presence, using the same scat samples, with the option to add further markers of interest. Such a one-stop-shop panel would considerably reduce processing times and cost.